2019
DOI: 10.1542/neo.20-7-e397
|View full text |Cite
|
Sign up to set email alerts
|

Gait Characteristics of Children Born Preterm

Abstract: Walking is a central skill of daily living. A delay in the onset of walking can be a sign of abnormal motor development. Further, abnormalities in gait can also affect physical functioning. Children born preterm are at significant risk for neurodevelopmental impairments; however, little is known about how preterm birth affects walking. This review describes current evidence of walking in children born preterm with a focus on the age at onset of walking and comparisons of gait characteristics of children born p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…In ID group, active and antagonistic muscles cannot coordinate, causing extensor muscles to tense and affecting motor performance. TD children have mature gait characteristics, with fully extended support legs and completely relaxed swinging legs (Albesher et al ., 2019). However, ID children's knee joints cannot fully extend, swinging legs cannot completely relax, and the muscle tension is abnormal, causing joint stiffness and a smaller range of lower limb movement, which are consistent with the action characteristics of the primary gait stage (Gallahue, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…In ID group, active and antagonistic muscles cannot coordinate, causing extensor muscles to tense and affecting motor performance. TD children have mature gait characteristics, with fully extended support legs and completely relaxed swinging legs (Albesher et al ., 2019). However, ID children's knee joints cannot fully extend, swinging legs cannot completely relax, and the muscle tension is abnormal, causing joint stiffness and a smaller range of lower limb movement, which are consistent with the action characteristics of the primary gait stage (Gallahue, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on gait development at 1 week of age in preterm and term pigs revealed only minor differences, although shorter strides and step lengths were present in preterm pigs after normalization for their smaller size (9). Interestingly, shorter strides are also observed in preterm infants, although such effects may disappear at later ages (1,6). No longitudinal postnatal locomotion studies comparing preterm and term counterparts are available in pigs or infants.…”
Section: Introductionmentioning
confidence: 91%
“…Previous studies on motor skills in preterm pigs showed that more days were required to achieve basic motor skills (time to first stand and walk), with lower overall physical activity level, compared with term pigs (9)(10)(11). Similarly, in preterm infants delayed or absent physical movement predict a delay in onset of first walking (6) and walking coordination (1,19). A previous study on gait development at 1 week of age in preterm and term pigs revealed only minor differences, although shorter strides and step lengths were present in preterm pigs after normalization for their smaller size (9).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations